2009
DOI: 10.1158/1078-0432.ccr-08-1720
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Angiotensin-Converting Enzyme Gene Polymorphism and Body Composition, Functional Performance, and Blood Biomarkers in Advanced Cancer Patients

Abstract: Purpose: Nutritional and functional outcome measures have been shown to vary in patients with chronic diseases according to the polymorphic alleles of angiotensin-converting enzyme (ACE), but little is known about the associations between ACE gene polymorphism (ACEGP) and the components of body composition, strength, and selected blood markers in advanced cancer patients (ACP). Experimental Design: Data were collected from an inception cohort of 172 newly diagnosed ACP with gastrointestinal and non^small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…In a 2-year longitudinal study (on 684 twins aged C73 years from the 1997 and 1999 surveys of the Longitudinal Study of Aging Danish Twins), the same group found no association between ACE genotypes and the baseline levels or time changes in selfreported physical performance (Frederiksen et al 2003b). In contrast, some studies have reported a positive association between the D allele and the following phenotypes: muscle mass in healthy inactive men and women (mean age 62 years) (Charbonneau et al 2008); lean mass (as well as handgrip force) in advanced cancer patients (mean age 65 years) (Vigano et al 2009); or appendicular fat-free mass in older women (mean age *67 years) (Lima et al 2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a 2-year longitudinal study (on 684 twins aged C73 years from the 1997 and 1999 surveys of the Longitudinal Study of Aging Danish Twins), the same group found no association between ACE genotypes and the baseline levels or time changes in selfreported physical performance (Frederiksen et al 2003b). In contrast, some studies have reported a positive association between the D allele and the following phenotypes: muscle mass in healthy inactive men and women (mean age 62 years) (Charbonneau et al 2008); lean mass (as well as handgrip force) in advanced cancer patients (mean age 65 years) (Vigano et al 2009); or appendicular fat-free mass in older women (mean age *67 years) (Lima et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Published findings are, however, controversial in old people. Some studies have reported a positive association between the D allele and lean body mass in the elderly (Charbonneau et al 2008;Lima et al 2011;Vigano et al 2009), although others found no association (McCauley et al 2010). Between-studies differences also exist for the potential association between ACE I/D genotypes and muscle strength/fitness, with both positive (Yoshihara et al 2009) and negative results (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative hypothesis would be that a proportion of patients were able to activate compensatory mechanisms aimed at conserving muscle. There is increasing evidence that gene polymorphisms are related to cancer cachexia susceptibility (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Published findings are also controversial in older people, starting with the possible association between this polymorphism and muscle mass. Some studies reported a positive association between the D allele and the following phenotypes: muscle mass in healthy inactive old men and women (Charbonneau et al 2008), lean mass (as well as handgrip force) in advanced cancer patients (Vigano et al 2009) or appendicular fat free fat (FFM) in old women (Lima et al 2011). In contrast, McCauley et al found no association with whole body and thigh lean mass in old Caucasians (McCauley et al 2010).…”
Section: Cross-sectional Genetic Association Studiesmentioning
confidence: 99%